Formation of Metastability of Pore Gas Hydrates in Frozen Sediments: Experimental Evidence - Evgeny Chuvilin; Dinara Davletshina; Boris Bukhanov; Aliya Mukhametdinova; Vladimir Istomin (Geosciences, 2022)
The Arctic permafrost and zones of hydrate stability may evolve to the conditions that allow gas hydrates to remain metastable for a long time due to self-preservation within 150 m depths. The behavior of relict (metastable) gas hydrates in frozen sediments is controlled externally by pressure and temperature and internally by the properties of hydrate particles and sediments. The sensitivity of the dissociation and self-preservation of pore gas hydrates to different factors is investigated in laboratory experiments. The observations focus on time-dependent changes in methane hydrate saturation in frozen sand samples upon the pressure dropping below phase equilibrium in the gas–hydrate–ice system. The preservation of pore gas hydrates in these conditions mainly depends on the initial hydrate and ice saturation, clay contents and mineralogy, salinity, and texture of sediments, which affect the size, shape, and structure distortion of hydrate inclusions. The self-preservation mechanism works well at high initial contents of pore ice and hydrate, low salinity, relatively low percentages of clay particles, temperatures below −4 °C, and below-equilibrium pressures. Nuclear magnetic resonance (NMR) measurements reveal considerable amounts of unfrozen pore water in frozen sediments that may hold for several days after the pressure drop, which controls the dissociation and self-preservation processes. Metastable gas hydrates in frozen sand may occupy up to 25% of the pore space, and their dissociation upon permafrost thawing and pressure drops may release up to 16 m3 of methane into the atmosphere per 1 m3 of hydrate-bearing permafrost.